2016
DOI: 10.1016/j.optlastec.2016.01.009
|View full text |Cite
|
Sign up to set email alerts
|

[INVITED] Epsilon-near-zero metalenses operating in the visible

Abstract: Several converging lenses working in the permittivity near to zero (ENZ) regime at optical frequencies are designed using an array of metaldielectric-metal plasmonic waveguides. These plasmonic waveguides show a dispersive nature that enable to mimic an effective ENZ medium when using the fast wave transverse electric (TE 1 ) mode near its cut-off wavelength. By arranging multiple plasmonic waveguides with the correct engineered dimensions, several metalenses, including graded index (GRIN) ones, and diffractiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Inspired by the recent development in ENZ metamaterials, several applications have been reported including nanocircuits [32,33], nonlinear control [34], impedance matched coaxial to waveguide transitions [35], antennas [36][37][38], levitation of particles [39], Fourier transformation [40], and beam shaping [41][42][43][44][45], to name a few, demonstrating that this type of metamaterial can be utilized in a variety of applications and frequency ranges. It is important to highlight that some of these applications have been developed by simply using the structural dispersion of a narrow hollow rectangular waveguide working near the cutoff of the fundamental TE 10 mode in order to emulate an ENZ medium, as it was used several decades ago to emulate plasmas at microwave frequencies using parallel-plate waveguides [46].…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the recent development in ENZ metamaterials, several applications have been reported including nanocircuits [32,33], nonlinear control [34], impedance matched coaxial to waveguide transitions [35], antennas [36][37][38], levitation of particles [39], Fourier transformation [40], and beam shaping [41][42][43][44][45], to name a few, demonstrating that this type of metamaterial can be utilized in a variety of applications and frequency ranges. It is important to highlight that some of these applications have been developed by simply using the structural dispersion of a narrow hollow rectangular waveguide working near the cutoff of the fundamental TE 10 mode in order to emulate an ENZ medium, as it was used several decades ago to emulate plasmas at microwave frequencies using parallel-plate waveguides [46].…”
Section: Introductionmentioning
confidence: 99%
“…Metamaterials have demonstrated that they allow successful control of the electromagnetic response of media, opening the gate to manipulation of wave propagation [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Within this realm, metamaterials with a relative permittivity near zero [known as epsilon near zero (ENZ)] exhibit fascinating features that have been recently studied in different frequency bands of the electromagnetic spectrum, mainly, microwaves, millimeter waves, and nearinfrared and optical frequencies [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Much of the attention is due to the fact that the waves traveling inside these media show almost "infinite" phase velocity and wavelength, with nearly uniform spatial phase variation, giving rise to unconventional phenomena such as tunneling, squeezing, and supercoupling [16].…”
Section: Introductionmentioning
confidence: 99%
“…Slits illuminated with the TE polarization exhibit a cut-off wavelength together with a resonance for transmission, enabling a fast phase modulation of the transmitted field, which is absent in the case of the TM polarization. Similarly, the dispersion of metal-dielectric-metal plasmonic waveguides is exploited to artificially mimic an epsilon-near-zero medium at optical wavelengths by working near the cut-off of the TE 1 mode [44].…”
Section: Gradient-index Metalensesmentioning
confidence: 99%